Quercetin Attenuates Atherosclerosis via Modulating Oxidized LDL-Induced Endothelial Cellular Senescence - Jiang, Yue-Hua; Jiang, Ling-Yu; Wang, Yong-Cheng; Ma, Du-Fang; Li, Xiao (Frontiers in Pharmacology, 2020)
Background and Aims: Endothelial senescence is an important risk factor leading to atherosclerosis. The mechanism of quercetin against endothelial senescence is worth exploring. Methods: Quercetin (20 mg/kg/d) was administered to ApoE-/- mice intragastrically to evaluate the effectiveness of quercetin on atherosclerotic lesion in vivo. In vitro, human aortic endothelial cells (HAECs) were used to assess the effect of quercetin on cellular senescence induced by oxidized low-density lipoprotein (ox-LDL). Transcriptome microarray and quantitative RT-PCR was conducted to study the pharmacological targets of quercetin. Results: ApoE-/- mice demonstrated obvious lipid deposition in arterial lumina, high level of serum sIcam-1 and IL-6, and high density of Vcam-1 and lower density of Sirt1 in aorta. Quercetin administration decreased lipid deposition in arterial lumina, serum sIcam-1 and IL-6 and Vcam-1 in aorta, while increased the density of Sirt1 in aorta of ApoE-/- mice. In vitro, quercetin (0.3, 1 or 3 μmol/L) decreased the expression of senescence-associated β-galactosidase and improved cell morphology of HAECs. And quercetin decreased the cellular apoptosis and increased mitochondrial membrane potential (ΔΨm) in dose-dependent manner, and decreased ROS generation simultaneously. Transcriptome microarray suggested 254 differentially expressed (DE) mRNAs (110 mRNAs were upregulated and 144 mRNAs were downregulated) in HAECs after quercetin treatment (fold change > 1.5, P < 0 .05, Que vs Ox-LDL). GO and KEGG analysis indicated nitrogen metabolism, ECM-receptor interaction, complement and coagulation cascades, p53 and mTOR signaling pathway were involved in the pharmacological mechanisms of quercetin against ox-LDL.